Dispersion system and dispersion method for dispersing nano titanium dioxide

By using a dispersion system of acid solution and nanocellulose suspension, ultrasonic dispersion of nanometer titanium dioxide solves the problems of high temperature, high pressure and electrolyte addition in the existing technology, and achieves efficient dispersion and low-cost production of nanometer titanium dioxide.

CN119349627APending Publication Date: 2025-01-24SHAN DONG NAMEIDE BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411543867.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When the prior art improves the dispersion performance of nano titanium dioxide, there are problems such as high temperature and high pressure requirements on equipment, increasing costs and adding electrolytes to affect the original performance.

Method used

A dispersion system including an acid solution and a nanocellulose suspension is used. By mixing the nanotitanium dioxide and the acid solution, adding the nanocellulose suspension, and performing ultrasonic dispersion, a uniformly dispersed nanotitanium dioxide dispersion suspension is formed.

Benefits of technology

The good decentralization of nano-titanium dioxide is realized, the particle size is between 50-100nm, and the method is green and environmentally friendly, and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349627A_ABST
    Figure CN119349627A_ABST
Patent Text Reader

Abstract

The invention discloses a dispersion system and a dispersion method for dispersing nano titanium dioxide, and belongs to the field of inorganic material dispersion. The dispersion system comprises an acid solution and a nanocellulose suspension; the dispersion method comprises but not limited to stirring, homogenizing, ultrasonic treatment, ball milling and the like to convert a titanium source into nano titanium dioxide so as to disperse the nano titanium dioxide into a cellulose suspension, and treating for a certain time to obtain a uniform dispersion system. According to the invention, different nano cellulose suspensions are adopted to disperse nano titanium dioxide, and the stable chemical property of the nano cellulose suspensions enables the nano titanium dioxide to be efficiently dispersed; the nano cellulose belongs to a biomass material, is rich in reserves, wide in source, renewable and degradable, and excellent in mechanical property, and the method is simple to operate, easy to implement, green and environment-friendly, and has great application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic material dispersion, and in particular relates to a dispersion system and a dispersion method for dispersing nano titanium dioxide. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Nano titanium dioxide is a white loose powder with strong UV shielding effect, good dispersibility and weather resistance. It can be used in cosmetics, functional fibers, plastics, coatings, paints and other fields as a UV shielding agent to prevent UV damage. Nano titanium dioxide dispersed by cellulose suspension has good dispersibility and titanium dioxide particles are not easy to agglomerate. It is mainly used in coatings, plastics, rubber, inks, textiles, cosmetics and other technical fields. In particular, it can improve printability and impermeability in the papermaking industry.

[0004] Dispersible nano titanium dioxide has strong ability to absorb ultraviolet rays, excellent photocatalytic performance, and has excellent characteristics such as high stability, high transparency, and high activity. It shows excellent characteristics in application, such as reducing usage, improving effects, not producing spots, not affecting color and gloss, and increasing fineness. Due to the small size of nano titanium dioxide particles, there are a large number of defects on the surface, the surface activity is large, and the particles in the medium are easy to agglomerate. Therefore, how to improve the dispersibility of nano titanium dioxide has become a key technical issue.

[0005] At present, the following methods are mainly used to improve the dispersion performance of nano-titanium dioxide: (1) By adding small molecule acids, its carboxyl group is grafted onto the surface of nano-titanium dioxide, and an ester bond is formed with the hydroxyl group of nano-titanium dioxide under high temperature and high pressure to form modified nano-titanium dioxide, so that it maintains good dispersion. (2) By adding surfactants and dispersants, the pH of the dispersion system is 5-10, so that titanium dioxide is not easy to agglomerate in the dispersion system for a long time, so that the nano-powder can be better dispersed. (3) By adjusting the pH value, a certain amount of surface charge is generated on the surface of the particles to form a double layer. The repulsive force between the double layers is conducive to the dispersion of the particles.

[0006] Although these methods improve the dispersibility of nano-titanium dioxide, they also have certain problems: for example, high temperature and high pressure require high equipment, leading to increased costs, and the addition of electrolytes can easily affect the original performance of nano-titanium dioxide. Therefore, how to efficiently disperse nano-titanium dioxide is still a problem that needs to be solved urgently. Summary of the invention

[0007] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a dispersion system and a dispersion method for dispersing nano titanium dioxide, which are green and environmentally friendly, have low cost, and have a small particle size after dispersion.

[0008] In order to achieve the above object, the technical solution of the present invention is:

[0009] In one aspect, the present invention provides a dispersion system for dispersing nano-titanium dioxide, comprising an acid solution and a nano-cellulose suspension.

[0010] Preferably, the nanocellulose suspension comprises a bacterial cellulose (BC) suspension or a cellulose nanofibril (CNF) suspension having an aspect ratio of 100-500.

[0011] Preferably, the mass fraction of the nanocellulose on an absolute dry basis to titanium dioxide is 0.5% to 5%.

[0012] Preferably, the acid solution is selected from one of lauric acid solution, stearic acid solution or fatty acid solution.

[0013] Preferably, the concentration of the acid solution is 1% to 5%.

[0014] Preferably, in the final nano-titanium dioxide dispersion suspension, the particle size of the nano-titanium dioxide is 50-500 nm, preferably 50-100 nm, and more preferably 50-60 nm.

[0015] In a second aspect, the present invention provides a method for dispersing nano-titanium dioxide, using the above-mentioned dispersion system, comprising the following steps:

[0016] (1) mixing nano-titanium dioxide with an acid solution and dispersing the mixture to obtain a preliminary dispersion system;

[0017] (2) Add the nanocellulose suspension to the preliminary dispersion system described in step (1) and perform ultrasonic dispersion to form a uniform and uniform titanium dioxide dispersion suspension.

[0018] Preferably, the nano titanium dioxide includes rutile type, anatase type and brookite type.

[0019] Preferably, the dispersion method in step (1) includes but is not limited to stirring, ultrasound, homogenization or ball milling.

[0020] Preferably, the dispersion concentration of the nano-titanium dioxide in the acid solution in step (1) is 5% to 20%, preferably 12%. If the dispersion concentration is too high, the dispersion effect is poor, and if it is too low, the dispersion efficiency will be affected.

[0021] Preferably, the acid solution in step (1) is selected from one of lauric acid solution, stearic acid solution or fatty acid solution.

[0022] Preferably, the concentration of the acid solution in step (1) is 1% to 5%.

[0023] Preferably, the treatment time in step (1) is 5 to 200 min, preferably 10 to 20 min.

[0024] Preferably, the ultrasonic dispersion time in step (2) is 20 to 40 minutes.

[0025] Preferably, the mass fraction of the absolute dry mass of the nanocellulose to titanium dioxide in step (2) is 0.5% to 5%.

[0026] Preferably, the final dispersion concentration of the nano-titanium dioxide in the acid solution and the nano-cellulose suspension in step (2) is 10-20%, preferably 10%.

[0027] Beneficial effects of the present invention:

[0028] (1) The surface of titanium dioxide contains a large number of hydroxyl groups. The acid solution can carboxylate titanium dioxide, thereby reducing the number of hydroxyl groups that are easy to agglomerate, making nano-titanium dioxide have good dispersibility. Secondly, since nanocellulose has excellent properties such as good biocompatibility, high mechanical strength, and good optical properties, the surface also contains a large number of hydroxyl groups, which can effectively improve the dispersibility of nano-titanium dioxide. The combined effect of acid solution and nanocellulose further enhances the dispersion effect.

[0029] (2) The nanocellulose described in the present invention is a biomass material with abundant reserves, wide sources, renewable and degradable properties, and excellent mechanical properties. The method described in the present invention is simple to operate, easy to implement, green and environmentally friendly, and has great application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0031] Figure 1 is the particle size distribution of the dispersion in Example 2 of the present invention;

[0032] Figure 2 is the particle size distribution of the dispersion in Example 5 of the present invention;

[0033] Figure 3 is the particle size distribution of the dispersion in Comparative Example 1 of the present invention;

[0034] Figure 4 is the particle size distribution of the dispersion in Comparative Example 2 of the present invention;

[0035] Figure 5 It is the particle size distribution of the dispersion in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0037] In the following examples and comparative examples, the dispersion concentration of titanium dioxide in the acid solution was 12%, and the final dispersion concentration of titanium dioxide in the acid solution and the nanocellulose suspension was 10%.

[0038] Example 1

[0039] Mix nano-titanium dioxide with 1% lauric acid solution, stir and disperse for 10 minutes to obtain a preliminary dispersion system;

[0040] Add 0.5% bacterial cellulose suspension by mass into the preliminary dispersion system, and perform ultrasonic dispersion for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide suspension with a particle size of 93 nm.

[0041] Example 2

[0042] Mix nano-titanium dioxide with a 2.5% lauric acid solution, stir and disperse for 10 minutes to obtain a preliminary dispersion system;

[0043] Add 0.5% bacterial cellulose suspension by mass into the preliminary dispersion system, and perform ultrasonic dispersion for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide suspension with a particle size of 59 nm.

[0044] Example 3

[0045] Mix nano-titanium dioxide with a lauric acid solution with a concentration of 5%, and stir and disperse for 10 minutes to obtain a preliminary dispersion system;

[0046] Add 0.5% bacterial cellulose suspension by mass into the preliminary dispersion system, and perform ultrasonic dispersion for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide suspension with a particle size of 84 nm.

[0047] Example 4

[0048] Mix nano-titanium dioxide with 1% lauric acid solution, stir and disperse for 10 minutes to obtain a preliminary dispersion system;

[0049] Add 0.5% by mass of cellulose nano-microfibril suspension to the preliminary dispersion system, and perform ultrasonic dispersion for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide suspension with a particle size of 313 nm.

[0050] Example 5

[0051] Mix nano-titanium dioxide with a 2.5% lauric acid solution, stir and disperse for 10 minutes to obtain a preliminary dispersion system;

[0052] Add 0.5% by mass of cellulose nano-microfibril suspension to the preliminary dispersion system, and perform ultrasonic dispersion for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide suspension with a particle size of 208 nm.

[0053] Example 6

[0054] Mix nano-titanium dioxide with a lauric acid solution with a concentration of 5%, and stir and disperse for 10 minutes to obtain a preliminary dispersion system;

[0055] Add 0.5% by mass of cellulose nano-microfibril suspension to the preliminary dispersion system, and perform ultrasonic dispersion for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide suspension with a particle size of 264 nm.

[0056] Example 7

[0057] Mix nano-titanium dioxide with a 2.5% lauric acid solution, stir and disperse for 10 minutes to obtain a preliminary dispersion system;

[0058] Add 0.25% bacterial cellulose suspension by mass into the preliminary dispersion system, and perform ultrasonic dispersion for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide suspension with a particle size of 232 nm.

[0059] Example 8

[0060] Mix nano-titanium dioxide with a 2.5% lauric acid solution, stir and disperse for 10 minutes to obtain a preliminary dispersion system;

[0061] Add 1% bacterial cellulose suspension by mass into the preliminary dispersion system, and perform ultrasonic dispersion for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide suspension with a particle size of 259 nm.

[0062] Example 9

[0063] Mix nano-titanium dioxide with a 2.5% lauric acid solution, stir and disperse for 10 minutes to obtain a preliminary dispersion system;

[0064] Add 2% bacterial cellulose suspension by mass into the preliminary dispersion system, and perform ultrasonic dispersion for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide suspension with a particle size of 358 nm.

[0065] Comparative Example 1

[0066] The nano-titanium dioxide was not mixed with any acid for pretreatment, and the aqueous dispersion was stirred and dispersed for 10 minutes to obtain a preliminary dispersion system; a bacterial cellulose suspension with a mass fraction of 0.5% was added to the preliminary dispersion system, and ultrasonic dispersion was performed for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide dispersion suspension with a particle size of 1.3 μm.

[0067] Comparative Example 2

[0068] Nano-titanium dioxide was mixed with a 2.5% lauric acid solution, and stirred and dispersed for 10 minutes to obtain a preliminary dispersion system; without adding any type of nano-cellulose, pure water was added to adjust the target solid content and ultrasonic dispersion was continued for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide dispersion suspension with a particle size of 6.6 μm.

[0069] Comparative Example 3

[0070] Nano-titanium dioxide was mixed with a 2.5% lauric acid solution, stirred and dispersed for 10 minutes to obtain a preliminary dispersion system; 0.5% by mass fraction of nano-cellulose crystals with an aspect ratio of about 50 were added, pure water was added to adjust the target solid content, and ultrasonic dispersion was continued for 20 to 40 minutes to obtain a uniformly dispersed nano-titanium dioxide dispersion suspension with a particle size of 3.5 μm.

[0071] Nano titanium dioxide dispersion performance test:

[0072] The dispersed nano titanium dioxide of Examples 1 to 9 and Comparative Examples 1-3 was bottled and left to stand at room temperature for 48 hours. The dispersion effect was reflected by the degree of stratification. The more obvious the stratification, the worse the dispersion effect; the less obvious the stratification or even no stratification was observed, the better the dispersion effect.

[0073] By comparing Examples 1-6 of the present invention, it is found that bacterial cellulose with a larger aspect ratio has a better dispersion effect than nanocellulose microfibrils with a smaller aspect ratio.

[0074] In addition, by comparing Examples 7-9 of the present invention, it is found that nanocellulose suspensions of different masses have significant dispersion effects on nano-titanium dioxide, and the optimal dosage is 0.5%.

[0075] Comparison between Example 1 and Example 2 shows that without adding acid, the particle size of the dispersion is 1.3 μm, which is much larger than that of Example 2, which is less than 59 nm.

[0076] Comparison between Comparative Example 2 and Example 2 shows that without adding nanocellulose, the particle size of the dispersion is 6.6 μm, which is much larger than that of Example 2, which is less than 59 nm.

[0077] Comparison of Comparative Example 3 with Example 2 shows that when nanocellulose crystals with an aspect ratio of less than 100 are added, the particle size of the dispersion is 3.5 μm, which is much larger than that of Example 5, which is less than 59 nm.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A dispersion system for dispersing nano titanium dioxide, characterized in that: including an acid solution and a nanocellulose suspension; The acid solution is selected from one or more of lauric acid solution, stearic acid solution or fatty acid solution; The nanocellulose suspension includes a bacterial cellulose suspension or a cellulose nanofibril suspension with an aspect ratio of 100-500.

2. The dispersion system according to claim 1, characterized in that The mass fraction of the nanocellulose relative to titanium dioxide on an absolute dry basis is 0.5% to 5%.

3. The dispersion system according to claim 1, characterized in that The concentration of the acid solution is 1% to 5%.

4. A method for dispersing nano titanium dioxide, characterized in that: The dispersion system for dispersing nano-titanium dioxide according to any one of claims 1 to 3 is used, comprising the following steps: (1) mixing nano-titanium dioxide with an acid solution and dispersing the mixture to obtain a preliminary dispersion system; (2) Adding the nanocellulose suspension to the preliminary dispersion system described in step (1) and performing ultrasonic dispersion to form a uniformly dispersed titanium dioxide suspension.

5. The dispersion method according to claim 4, characterized in that The nano titanium dioxide includes rutile type, anatase type and brookite type.

6. The dispersion method according to claim 4, characterized in that The dispersion concentration of the nano-titanium dioxide in the acid solution in step (1) is 5% to 20%; The acid solution in step (1) is selected from one or more of lauric acid solution, stearic acid solution or fatty acid solution; The concentration of the acid solution in step (1) is 1% to 5%.

7. The dispersion method according to claim 4, characterized in that The treatment time in step (1) is 5-200 min.

8. The dispersion method according to claim 4, characterized in that The mass fraction of the nanocellulose in step (2) relative to titanium dioxide is 0.5% to 5%; In step (2), the ultrasonic dispersion time is 20 to 40 minutes.

9. The dispersion method according to claim 4, characterized in that The final dispersion concentration of the nano-titanium dioxide in the acid solution and the nano-cellulose suspension in step (2) is 10-20%.

10. The dispersion method according to claim 4, characterized in that In the titanium dioxide dispersion suspension in step (2), the particle size of nano-titanium dioxide is 50-500 nm, preferably 50-100 nm.